1969
DOI: 10.1007/bf01984664
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of stiffness in human joints

Abstract: Goddard, Dowson, Longfield and Wright, The measurement o/sti~ness in human joints 229 ConclusionsThe small scale capillary viscometer has proved to be a versatile and convenient instrument to use for the determination of the flow curves of small quantities of polymer melts. The piston speed can be rapidly and accurately set over a speed range of I000:1. The melt pressure is measued directly above the capillary, which has the advantage over measuring the pressure in the piston face, or the thrust on the piston,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Goddard et al (1969), in our Unit, employed a sinosoidal motion to investigate the knee, and measured the resistive torque, plotting it in relation to angular displacement. To overcome inertial effects, Thompson et al (1978) produced an alternative knee arthograph in which the patient's knee was flexed horizontally with the patient lying on his side.…”
Section: Stiffnessmentioning
confidence: 99%
“…Goddard et al (1969), in our Unit, employed a sinosoidal motion to investigate the knee, and measured the resistive torque, plotting it in relation to angular displacement. To overcome inertial effects, Thompson et al (1978) produced an alternative knee arthograph in which the patient's knee was flexed horizontally with the patient lying on his side.…”
Section: Stiffnessmentioning
confidence: 99%
“…The hysteresis was likely due to the plastic properties of the joint, with viscous effects negligible at low joint speed. 11,28 Future studies can be designed to study the viscoelastic properties of finger joints, for example, by collecting and analyzing torque-angle data over a wide range of joint speeds. The robot system developed in this study could be conveniently configured to perform such well-controlled experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…Electromyographic and anesthesia studies have shown that that finger joint movement with a low passive speed did not produce muscle contraction. 11,17,31,32 In addition, any voluntary muscle contraction was easily detectable with the continuous monitoring of the torque-angle data on the computer screen, because slight muscle activity would cause a large deviation from the highly reproducible passive torque-angle loops (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations